Is (critical) health literacy a key to better psychosomatic functioning in patients with inflammatory bowel disease? Testing a mediation model - Papp-Zipernovszky, Orsolya; Horvát, Barbara; Dávid, Anett; Rafael, Beatrix; Tóth-Njers, Sanela; Strausz, Dávid; Gyóllai, Mátyás; Molnár, Tamás; Sallay, Viola; Konkolÿ Thege, Barna; Martos, Tamás (Frontiers in Psychiatry, 2026)
IntroductionChronic illnesses such as inflammatory bowel disease (IBD) require continuous self-management, often under emotionally and physically taxing conditions. While health literacy and health self-efficacy are known to support disease adaptation, their combined role in psychosomatic functioning, especially under varying levels of depression, remains underexplored. This study examined how health literacy, health self-efficacy, and depressive symptoms influence symptom severity and life satisfaction in patients with IBD.MethodsA cross-sectional survey of 393 patients with IBD (60.7% with Crohn’s disease; 56% female; mean age = 40.75) was conducted at a gastroenterology outpatient clinic in Hungary. Standardized questionnaires assessed health literacy, health self-efficacy, depression, symptom severity, and satisfaction with life. Structural equation modeling was used to test a mediation model. Multigroup analyses explored the stability of the model across subgroups defined by depressive symptom levels, disease status (relapse vs. remission), and types of diseases.ResultsCritical health literacy predicted higher health self-efficacy, which was associated with lower symptom severity and, in turn, greater life satisfaction. This indirect pathway remained significant after controlling demographic variables. Multigroup analyses showed that these relationships were stronger among patients in relapse and those with elevated depression, suggesting increased psychological sensitivity in these subgroups. No difference was found between types of disease.DiscussionThe findings underscore the importance of critical health literacy and health self-efficacy as interconnected psychological resources in chronic illness self-management. Strengthening these capacities may reduce symptom burden and enhance well-being, particularly in times of relapse and periods of psychological vulnerability. The results support a shift toward integrated, psychosocially informed care models for IBD.